(untitled) (Global Journal of Science Frontier Research, 2016)
To keep animals healthy, traditional healing practices have been applied for centuries and have been passed down orally from generation to generation. Rural tribal people generally depend on plants for curing their livestock due to the problem of animal health delivery system. In Ethiopia, the use of ethno veterinary practices to treat and control livestock diseases is an old and important practice. The field survey was carried out in Wolaita and Dawuro Zones of SNNPR, Ethiopia to document ethno veterinary practices in the area. A total of 89 individual healers were purposively selected and interviewed based on their knowledge of using traditional medicine to cure their animals. Descriptive statistics was used to analyze and summarize the ethno-botanical data. Forty plants, which have medicinal value against a total of 27 livestock diseases, were reported and botanically identified as belonging to various 25 plant families. Leaves (57.14%) were the major plant parts used in the study areas.